PERALIHAN AKAD NIKAH BERWALI HAKIM PENGGANTI WALI NASAB MENURUT HUKUM ISLAM (Studi Di Kantor Urusan Agama Kecamatan Sungailiat Semester 1 Tahun 2023) - Tristina, Tristina; Suhendra, Darmiko; Nurdin, Muhamad (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Marriage is a teaching based on the Koran and Sunnah in various ways of expressing it. In carrying out a wedding, of course you have to fulfill the pillars of marriage. One of the pillars of marriage is having a guardian. Guardianship in marriage is carried out by the guardian of the lineage and the guardian of the judge. The main problem in this research is the marriage contract which should be carried out by the nasab guardian or natural guardian, whereas for several reasons the consent in the marriage contract is carried out by the judge's guardian with the main problem being what is the reason for the transfer of the marriage contract to a judge replacing the nasab guardian at the Office of Religious Affairs Sungailiat District and what is the view of Islamic law regarding the position of guardian judge. This research is qualitative research using a juridical-empirical approach. The sources of this research are Primary Legal Materials (observations and interviews), Secondary Legal Materials (books, journals and other scientific works), data preparation is carried out by studying activities to understand an object from an event based on knowledge and previously known ideas. Based on the results of research on the reasons for the transition to a marriage contract with a judge as guardian according to Islamic law, marriage data for semester 1 of 2023 at the KUA, Sungailiat District, there are several factors that cause this transition, namely due to a break in the lineage, namely the guardian dies, the guardian of the lineage is unseen, namely the whereabouts of the guardian of the lineage are unknown. , the guardian of the lineage is of a different religion, the guardian of the lineage is adholic or reluctant, the child was born out of wedlock and the guardian is carrying out the Hajj or Umrah. It is for these reasons that the marriage contract is carried out with a guardian judge. The position of the judge's guardian according to Islamic law is that the judge's guardian acts as a substitute guardian in the event of the absence of a guardian and his status is valid as long as the terms and conditions apply. Key words: Guardian of Nasab, Guardian Judge, Islamic Law